Diploporite (Echinodermata, Blastozoa) thecal attachment structures from the Silurian of southeastern Indiana. (January 2014) - Thomka, James R.; Brett, Carlton E.
Abstract : Taxonomic descriptions of diploporites from the middle Silurian of eastern Laurentia have focused nearly entirely on thecal plating, with minimal description or figuring of attachment structures. A recently discovered hardground surface within the Wenlock-age (Sheinwoodian) Massie Formation that is encrusted by numerous well-preserved pelmatozoan holdfasts, including structures identifiable as diploporite thecal attachments, provides an opportunity to document the morphology of these rarely described structures. Moderately thin-walled structures with a parabolic, depressed central area composed of seven distinct marginal plates with prominent pores appear to represent thecal attachments of the broad-based trematocystinid holocystitid Paulicystis . Thick-walled, steep-sided structures composed of five to seven fused or partially fused plates with less prominent pores, a deep stelar depression, and radiating canals appear to represent thecal attachments of undetermined, possibly holocystinid or pentacystinid holocystitids. All diploporite holdfasts are cemented to fine-grained, well-sorted skeletal substrates on elevated crests of the hardground surface, but are not found on microbioherms.